2021
DOI: 10.1016/j.jbef.2021.100549
|View full text |Cite
|
Sign up to set email alerts
|

Individual investors’ trading behavior in Moscow Exchange and the COVID-19 crisis

Abstract: This article presents the first study of Russian individual investors’ aggregate equity trading behavior using novel data from Moscow Exchange, with a focus on the COVID-19 episode. Aggregate Russian individual bought the dip during the COVID crash in March–April 2020. While this can be accounted for by their regular contrarian trading traits, they remained as net buyers until the market fully recovered, a sign of sophistication in striking contrast to views that characterized individual investors as noise tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The study revealed that experts’ financial advice prompts investors with traits of openness and neuroticism to trade more frequently than investors who possess other traits like extraversion and conscientiousness. Several studies have also been undertaken during the period of COVID-19 to check the impact of pandemic on the trading behaviour of noise traders (Djalilov and Ülkü, 2021; Guo et al , 2021).…”
Section: Content Analysismentioning
confidence: 99%
“…The study revealed that experts’ financial advice prompts investors with traits of openness and neuroticism to trade more frequently than investors who possess other traits like extraversion and conscientiousness. Several studies have also been undertaken during the period of COVID-19 to check the impact of pandemic on the trading behaviour of noise traders (Djalilov and Ülkü, 2021; Guo et al , 2021).…”
Section: Content Analysismentioning
confidence: 99%
“…Based on French data, Foucault et al (2011) give evidence that retail investors increase stock return volatility as they are noise traders. Bertero et al (1990) clarifies that in crisis, psychological factors controlled the investor as there is a few of information available, Moreover, Djalilov et al (2021) mentioned that when COVID-19 appears, this pandemic has resulted in a significant increase in retail investor presence in stock markets around the world. Retail investors are now recognized as a market-driving force as of early 2021.…”
Section: Introductionmentioning
confidence: 98%
“…These factors include easy monetary policy of many central banks, falling rates on debt instruments and bank deposits, COVID-19-related fiscal relief packages, and the development of investment platforms designed for trading via mobile apps and for discussion in social networks. Stock exchanges globally have experienced an increase in the share of retail investors in trading volume [1]. For example, in Russia, the share of retail investors in the trading volume of domestic stocks increased from 34% in 2013 to 40% in 2020, and it reached 43% in mid-2021 ( [1]; MOEX bulletins).…”
Section: Introductionmentioning
confidence: 99%
“…Stock exchanges globally have experienced an increase in the share of retail investors in trading volume [1]. For example, in Russia, the share of retail investors in the trading volume of domestic stocks increased from 34% in 2013 to 40% in 2020, and it reached 43% in mid-2021 ( [1]; MOEX bulletins). In the largest stock market of the US, the share of retail investors increased from 13% in 2013 to 24% in mid-2021 (source: Bloomberg Intelligence) (https://www.bloomberg.com/news/articles/2021-11-17/retail-traders-retreat-as-choppymarkets-challenge-easy-profits).…”
Section: Introductionmentioning
confidence: 99%